Strategi Pembelajaran Meaningful Instructional Design Untuk Meningkatkan Hasil Belajar Biologi Kelas X Siswa SMK Negeri 2 Botomuzoi Tahun Pembelajaran 2024/2025 - Desrita Hulu; Angeli Valentina Telaumbanua; Agnes Renostini Harefa (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
The low biology learning outcomes of 10th-grade students at SMK Negeri 2 Botomuzoi is the primary problem driving this research. The purpose of this research is to describe the biology learning process and improve student learning outcomes through the implementation of the Meaningful Instructional Design learning strategy. This classroom action research was conducted in two cycles, with 10 10th-grade ATPH students as subjects. Data collection was conducted through observation sheets, learning process questionnaires, learning outcome tests, and documentation. The results showed a significant improvement in the learning process, from 61.13 percent in the first cycle to 77.71 percent in the second cycle. Student learning outcomes also increased from an average score of 68.5 in the first cycle to 85.3 in the second cycle. These findings indicate that the Meaningful Instructional Design strategy is effective in increasing student engagement and understanding of biology concepts, particularly in topics related to ecosystems and the impacts of pollution. This research provides practical contributions for teachers in optimizing meaningful biology learning in vocational high schools.